MEDICAL STUDENTS MOTIVATION AFTER TAKING A POST-TEST IN PROBLEM-BASED LEARNING - Nola Agina Br Ginting; Ratih Yulistika Utami (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: Student prior knowledge on the tutorial process (problem-based learning) is different from each batch, which affects the ability to determine the learning issue. Assessment is one of the factors that influence student motivation to learn in the tutorial; increasing students’ motivation is an essential target in PBL. The objective of this study was to determine the effect of applying a post-test at the tutorial on students’ learning motivation of FM UMSU in order to achieve the learning objectives of PBL.Methods: This research was a quantitative study; experimental methods with post-test only control group design. This study measured the students' learning motivation using the Motivated Strategies for Learning Questionnaire (MSLQ). Samples were students of FM UMSU class 2013, divided into two groups randomly. Data were analyzed using the Mann-Whitney test.Results: Assessment should motivate students’ learning. However, in PBL, several factors that affect students’ motivation as well as assessment. Those factors are group dynamics, scenario, and tutor’s performance that should be controlled. The validity and reliability of the assessment are also crucial issues that affect the results.Conclusion: A proper assessment should be able to motivate students to learn. However, in PBL, several factors affect students’ motivation as well as assessment, namely group dynamics, scenario, and tutors’ performance that should be controlled. The assessment itself refers to their validity and reliability so that researchers should consider several issues before constructing the MCQs in PBL, for example, the content, type and timing of the assessment in order to motivate students to study harder by applying a strategic approach.